2022
DOI: 10.1177/0739456x211072527
|View full text |Cite
|
Sign up to set email alerts
|

Missing the Housing for the Trees: Equity in Urban Climate Planning

Abstract: This paper examines equity’s incorporation into Climate Action Plans (CAPs), an increasingly important part of the urban sustainability planning landscape. We conduct a content analysis of 170 California CAPs and compare the plans’ treatment of equity to city characteristics such as size and income inequality. We find that equity language correlates with an increased presence of more systemic policy interventions, such as dense and/or affordable housing, in CAPs. However, the majority of CAPs “miss the housing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 65 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Additionally, there is still uncertainty and lack of consensus around what equity means in a municipal climate action planning context (Angelo et al, 2020), which was highlighted by participants who felt there are limited tangible tools and resources to understand the intersections of justice, equity, and sustainability in climate action planning and how to apply this understanding. This suggests that while there are steps being taken to address the equity deficit, municipalities still require practical knowledge, resources, and tools of how to do this work, meaningfully and appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is still uncertainty and lack of consensus around what equity means in a municipal climate action planning context (Angelo et al, 2020), which was highlighted by participants who felt there are limited tangible tools and resources to understand the intersections of justice, equity, and sustainability in climate action planning and how to apply this understanding. This suggests that while there are steps being taken to address the equity deficit, municipalities still require practical knowledge, resources, and tools of how to do this work, meaningfully and appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Even where climate action planning occurs on a large scale, equity issues are often left out. For example, Angelo et al (2022) found that in 170 local climate action plans in California, 39% of plans made no mention of equity.…”
Section: Climate Action Planningmentioning
confidence: 99%
“…A major concern of sociological scholarship resides in the level of coverage and equity in climate action planning (Angelo et al., 2022; Roy et al., 2022). Since most climate action planning occurs at the city level, many cities, smaller towns and rural regions lack protection.…”
Section: The Forms Of Climate Actionmentioning
confidence: 99%
See 1 more Smart Citation